Selecting and structuring semantic resources to support SMEs knowledge communities - Simões, Dora
Knowledge management intrinsically involves communication and information sharing, which can be strongly affected by the context in which it is viewed and interpreted. This situation gets worst when complex domains. are considered, as it is the case of the Construction Industry domains. The development of ontologies to unify and to put into context the different concepts and terms of the sometimes rather traditional and locally coloured construction industry domains is a necessary step to avoid misinterpretations and inefficient communication. The KNOW-CONSTRUCT project decided, as an approach to this task, to re-use, as far as possible, existing ontologies, classification systems and other semantic resources in order to develop a system that may come to contribute to standards and to the integration, management and reuse of the area specific knowledge via a common knowledge base in order to consolidate and provide access to integrated knowledge, making community emergent knowledge a significant added value. It aims at developing a methodology of common Construction Industry Knowledge (CIK) representation applicable to large sets of SMEs in the construction industry as a basis for the establishment of a knowledge community.